Regulatory Non-coding RNAs Network in Non-alcoholic Fatty Liver Disease - Sulaiman, Siti Aishah; Muhsin, Nor I. A.; Jamal, Rahman (Frontiers in Physiology, 2019)
Non-alcoholic fatty liver disease (NAFLD) spectrum comprises simple steatosis and non-alcoholic steatohepatitis (NASH) that can lead to fibrosis and cirrhosis. The patients usually have no history of excessive alcohol consumption and other etiologies that can cause fatty liver. Understanding of the pathophysiology of NAFLD has revealed that noncoding RNAs (ncRNAs) play significant roles in modulating the disease susceptibility, pathogenesis and progression. Currently, the ncRNAs are grouped according to their sizes and their regulatory or housekeeping functions. Each of these ncRNAs has a wide range of involvement in the regulation of the genes and biological pathways. Here, we briefly review the current literature the regulatory ncRNAs in NAFLD pathogenesis and progression, mainly the microRNAs, long noncoding RNAs and circular RNAs. We also discuss the co-regulatory functions and interactions between these ncRNAs in modulating the disease pathogenesis. Elucidation of ncRNAs in NAFLD may facilitate the identification of early diagnostic biomarkers and development of therapeutic strategies for NAFLD.